Characterization of Heat Shock Protein-Specific T Cells in Atherosclerosis - Ford, Pauline (American Society for Microbiology, 2005)
A role for infection and inflammation in atherogenesis is widely accepted. Arterial endothelium has been shown to express heat shock protein 60 (HSP60) and, since human (hHSP60) and bacterial (GroEL) HSP60s are highly conserved, the immune response to bacteria may result in cross-reactivity, leading to endothelial damage and thus contribute to the pathogenesis of atherosclerosis. In this study, GroEL-specific T-cell lines from peripheral blood and GroEL-, hHSP60-, and Porphyromonas gingivalis-specific T-cell lines from atherosclerotic plaques were established and characterized in terms of their cross-reactive proliferative responses, cytokine and chemokine profiles, and T-cell receptor (TCR) Vβ expression by flow cytometry. The cross-reactivity of several lines was demonstrated. The cytokine profiles of the artery T-cell lines specific for GroEL, hHSP60, and P. gingivalis demonstrated Th2 phenotype predominance in the CD4 subset and Tc0 phenotype predominance in the CD8 subset. A higher proportion of CD4 cells were positive for interferon-inducible protein 10 and RANTES, with low percentages of cells positive for monocyte chemoattractant protein 1 and macrophage inflammatory protein 1α, whereas a high percentage of CD8 cells expressed all four chemokines. Finally, there was overexpression of the TCR Vβ5.2 family in all lines. These cytokine, chemokine, and Vβ profiles are similar to those demonstrated previously for P. gingivalis-specific lines established from periodontal disease patients. These results support the hypothesis that in some patients cross-reactivity of the immune response to bacterial HSPs, including those of periodontal pathogens, with arterial endothelial cells expressing hHSP60 may explain the apparent association between atherosclerosis and periodontal infection.